Cultural Differences in Aggression: A Case Study in Bangladesh (Journal of Life and Earth Science, 2011)
The present study was to examine gender and cultural differences in aggressive behaviour in the context of Bangladesh. Sample was selected from two cultural backgrounds such as Bengali culture and Santal culture in different areas of Rajshahi District. A total of 160 respondents were randomly selected from Santal and Bengali culture populations. A 2×2×2 factorial design representing two levels of cultural group (Bengali / Santal), two levels of residential background (urban / rural) and two levels of sex (male / female) was used in the study. The Measure of Aggressive Behaviour was used for data collection. The data were analyzed using Analysis of Variance. It was found that Bengali respondents expressed more aggression than Santal respondents. Residential background and sex differences were also observed. Thus culture emerged as an important factor in aggression. Key words: Aggression; antisocial behaviour; gender differences; residential background; culture DOI: 10.3329/jles.v3i0.7445 J. Life Earth Sci., Vols. 3-4: 43-46, 2009